Microscale iron and sulphur isotopic compositions reveal pyritization pathways during early diagenesis - Virgil Pasquier; Johanna Marin-Carbonne; Thomas Giunta; Livio Ruffine; Itay Halevy (Communications Earth & Environment)
Abstract Sedimentary pyrite iron and sulphur isotope compositions (δ56FePYR, δ34SPYR, Δ33SPYR) are commonly used to reconstruct global ocean properties and the evolving oxidation state of Earth’s surface, motivating exploration of impacts of diagenesis on pyrite-based proxies. Along with auxiliary petrographic and porewater data, we present coupled microscale δ56FePYR-δ34SPYR-Δ33SPYR in accumulating sediments on the oxic margin of the Black Sea. The coevolution of microscale δ56FePYR-δ34SPYR-Δ33SPYR distributions provides insight into porewater S species production, consumption, and buildup on pyritization pathways. “Early” pyrite is characterized by low δ56FePYR and δ34SPYR values consistent with microbially-mediated iron and sulphate reduction and iron (oxyhydr)oxide sulphidization at low sulphide-to-iron ratios. In contrast, “sulphidic zone” pyrite displays distinct late-stage morphologies and higher δ56FePYR and δ34SPYR, which reflect sulphide accumulation at the sulphate-methane transition zone and direct sulphidization of residual iron phases. We propose that coupled δ56FePYR-δ34SPYR-Δ33SPYR distributions constrain pyritization pathways and microbial and physico-chemical aspects of the depositional environment.